2014
DOI: 10.1016/j.jped.2013.08.007
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factors associated with wheezing in the first year of life

Abstract: the main risk factors associated with wheezing in Fortaleza were respiratory infections and family history of asthma. Knowing the risk factors for this disease should be a priority for public health, in order to develop control and treatment strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
1
5

Year Published

2016
2016
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 23 publications
3
19
1
5
Order By: Relevance
“…Maternal allergic rhinitis was found as a risk factor for recurrent wheezing, and paternal allergic dermatitis for wheezing ever. These results agree with results from others EISL studies (7,9), where allergic diseases were risk factors for wheezing ever and recurrent wheezing.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Maternal allergic rhinitis was found as a risk factor for recurrent wheezing, and paternal allergic dermatitis for wheezing ever. These results agree with results from others EISL studies (7,9), where allergic diseases were risk factors for wheezing ever and recurrent wheezing.…”
Section: Discussionsupporting
confidence: 93%
“…Prevalence of wheezing ever in infants in our study was 31.2%, similar prevalence compared to others EISL studies conducted in Spain, in the city of Salamanca, which found 32.3% (14) and in Netherlands, 28.5% (7), but less prevalence than in Latin America countries, where mean prevalence was 47.3% (15). Prevalence of recurrent wheezing was 12.3%, similar to the other Spanish EISL study (14), but lower than other European and Latin American studies (7,9).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Of the remaining 50 studies, 14 studies were excluded because they were reviews or pooled studies, studied risk factors for wheezing but did not provide prevalence data, did not define the outcome or provide wheezing cases, and were not community-based studies (14 in MEDLINE), and 28 were excluded because their study population was older than two years old (25 in MEDLINE and 3 in SCOPUS). Finally, eight studies were included (15,16,(18)(19)(20)(22)(23)(24).…”
Section: Resultsmentioning
confidence: 99%
“…[56] Acute lower respiratory tract infection (ALRTI) due to respiratory syncytial virus[7] and rhinovirus[8] in early life has been implicated as contributing to asthma. In recent years, significant evidence from birth cohort studies has been indicating that reduced neonatal lung function and increased airway responsiveness are associated with respiratory symptoms and asthma later in life.…”
Section: Introductionmentioning
confidence: 99%